Сегментная структура плечевого сплетения некоторых Galliformes - Сыч, В.Ф. (Вестник зоологии, 1980)
The same type of the brachial plexus quantitative composition was determined in five Galliform.es species. Cranial displacement of the plexus and its axial segment along the spine was found in Phasianus colchicus, Perdix perdix and Coturnix coturnix. N. supracoracoideus, n. scapulo-humeralis and n. radialis are characterized by stability in the number of initial segments. Homologous nerves of the brachial plexus ventral trunk are rather different in segment composition. These differences are partially explained by the secondary fusion of n. medio-ulnaris and n. pectoralis into a single trunk.